Phaeocystis, Major Link in the Biogeochemical Cycling of Climate-Relevant Elements 2007
DOI: 10.1007/978-1-4020-6214-8_2
|View full text |Cite
|
Sign up to set email alerts
|

A taxonomic review of the genus Phaeocystis

Abstract: Phaeocystis is recognized both as a nuisance and as an ecologically important phytoplankton species. Its polymorphic life cycle with both colonial and Xagellated cells causes many taxonomic problems. Sequence variation among 22 isolates representing a global distribution of the genus has been compared using three molecular markers. The ribulose-1,5-bisphosphate carboxylase/oxygenase (RUBISCO) spacer is too conserved to resolve species. The most conserved 18S ribosomal deoxyribonucleic acid (rDNA) analysis sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
17
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 35 publications
(31 reference statements)
1
17
1
Order By: Relevance
“…Of the most OTU‐rich groups, the group with the highest proportion of OTUs matching environmental sequences was Phaeocystaceae and Chrysochromulinaceae (Table S4a). Within both of these groups, several morphological forms have been recognized that are not yet in culture and genetically characterized (Jensen ; Medlin and Zingone ). Our result, that several OTUs had best match with DNA sequences or reads from environmental samples, supports previous studies showing that there is a large diversity of haptophytes that remains to be cultured and DNA sequence determined (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Of the most OTU‐rich groups, the group with the highest proportion of OTUs matching environmental sequences was Phaeocystaceae and Chrysochromulinaceae (Table S4a). Within both of these groups, several morphological forms have been recognized that are not yet in culture and genetically characterized (Jensen ; Medlin and Zingone ). Our result, that several OTUs had best match with DNA sequences or reads from environmental samples, supports previous studies showing that there is a large diversity of haptophytes that remains to be cultured and DNA sequence determined (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…antarctica has different biogeographical ecotypes [30, 31] and it was recently shown that the species’ genetic variability is high over space and time, even among clones isolated from the same P . antarctica bloom [29].…”
Section: Resultsmentioning
confidence: 99%
“…2005, Boenigk et al. 2006, Medlin and Zingone 2007). In an evolutionary context, cryptic and pseudo‐cryptic species may represent species that (i) have not evolved evident morphological differences because there is no selective pressures on morphology (Bickford et al.…”
mentioning
confidence: 99%